Morpho-biology of Pomadasys auritus from bottom longline catches in Tarakan waters, North Kalimantan, Indonesia - MUHAMMAD FIRDAUS; ABDUL JABARSYAH IBRAHIM; GAZALI SALIM; M. GANDRI HARYONO; STEPHANIE BIJA; NAOMI RASMALEMTA GIRSANG; MUJIYANTO MUJIYANTO; SITTI HARTINAH; RETNO HARTATI; ROZI ROZI (Society for Indonesian Biodiversity, 2025)
Abstract. Firdaus M, Ibrahim AJ, Salim G, Haryono MG, Bija S, Girsang NR, Mujiyanto M, Hartinah S, Hartati R, Rozi. 2025. Morpho-biology of Pomadasys auritus from bottom longline catches in Tarakan waters, North Kalimantan, Indonesia. Biodiversitas 26: 5870-5880. Pomadasys auritus is an economically important demersal species in Tarakan waters, yet the biological information required for effective stock management remains limited. This study describes the morphological characteristics and estimates the growth parameters of P. auritus captured by bottom longlines. Sampling was conducted from November 2022 to February 2023 at the Selumit Landing Site, yielding 219 specimens across 16 fishing trips. Morphological identification was based on diagnostic opercular traits, fin-ray formulas, and body colouration. Growth parameters were estimated using the von Bertalanffy Growth Function (VBGF), resulting in an asymptotic length (L?) of 109.53 cm, a growth coefficient (K) of 0.0194 day?¹, and a theoretical age at zero length (t?) of 0.823 days. These values indicate slow growth and a tendency to reach large body sizes, traits characteristic of long-lived demersal fishes that are naturally susceptible to fishing pressure. The catch composition, dominated by sub-adult and adult individuals, suggests that Tarakan waters serve as an important habitat supporting the growth phase of this species. This pattern underscores the need for cautious management, particularly because slow-growing species are vulnerable to rapid stock depletion under sustained exploitation. The dataset generated in this study provides an essential biological baseline that can support more accurate stock assessments and inform the development of appropriate management strategies for demersal fisheries in northern Kalimantan. Given that the dataset is derived solely from landing-site observations, future studies should incorporate reproductive biology, feeding ecology, environmental conditions, and mortality parameters to enhance population models and strengthen the scientific basis for managing P. auritus in Tarakan waters.